LAW AND NATURE FROM THE PERSPECTIVE OF THE SUNGAI TEKAI INDIGENOUS COMMUNITY - Norasmah, Othman; Hanim, Kamaruddin; Rubiah, Ajan; Siti Waffa, Abdul Jabar; Viviien Yew, Wong Chin; Abd Hair, Awang; Rohaida, Nordin (Future Academy, 2019)
The knowledge and awareness of the legal rights and limitations towardsthe utilization of natural resources including flora and fauna is lacking or non-existent amongst the Sungai Tekai indigenous community. Therefore, this study aims to answer the question as to whether there is any knowledge, little or otherwise, of environmental protection from any aspect including legal amongst the Sungai Tekai indigenous community. This study is quantitative in nature. The population of this study is the Sungai Tekai indigenous community in Pahang, Malaysia. Random sampling techniques was deployed in this study. The findings reveal that less than 10% of the Sungai Tekai indigenous community are aware of the rights and limitations to utilizing the natural resources in their area. Hence, there is a need to engage the Sungai Tekai communities in environmental awareness on their legal rights and constraints on environmental resources and usage.